Optimasi Geometri Lereng dengan Evaluasi Nilai Faktor Keamanan Menggunakan Software Geostudio - Gilang Wahyu Kottama; Agata Iwan Candra; Arif Rivianto; Muhammad Rifqi Fatkhur Rohman; M Rizal Agus Joko Budiawan; M Sousa Taufani; M Wildan Prasetyo (Jurnal Manajemen Teknologi & Teknik Sipil, 2023)
The slopes of the Widas watershed in Kutorejo Village, Bagor District, Nganjuk Regency were hit by a landslide, damaging a 50-meter-long road. This damage has an impact on the activities and mobility of residents. The impact of landslides caused enormous losses, both infrastructure damage and loss of life. Several studies have been carried out, in determining slope stability it is necessary to observe at the research location and determine the type of soil, soil consistency, and soil shear strength parameters. This research aims to determine the value of the safety factor (FK) on the slopes of the Widas River. This research began by conducting a case study, including interviews, collecting field survey data, taking soil samples, and laboratory testing. Slope stability analysis was carried out using Geostudio software. The research results show that the soil type is classified as Poorly Graded Sand (SP), and the soil consistency is classified as Non-Plastic soil with a liquid limit of 26.093 and a shear angle of 20° - 30°. Slope improvements were carried out by changing the slope geometry until a slope ratio of 1V:2H was obtained by creating two slope core models. The FK value increased from 1.007 to 1.107 and 1.437 to 1.585 under pore water pressure conditions. Thus, the slope modeling obtained can be used to overcome landslide problems.